ISOLATION AND EVALUATION OF ANTAGONISTIC POTENTIAL OF INDIGENOUS OF INDIGENOUS OF INDIGENOUS TRICHODERMA TRICHODERMA TRICHODERMA ISOLATES AGAINST SOIL BORNE PATHOGENS CAUSING RHIZOME ROT IN TURMERIC (Curcuma longa Curcuma longa Curcuma longa L.) AND GINGE - NAVYASHREE, S. E.; KOULAGI , SUMANGALA; SHASHI KUMAR, H. M. (The Bioscan, 2018)
Total of twenty five indigenous isolates of Trichoderma species were isolated from rhizosphere soils of turmeric and ginger grown in different locations of Belagavi and Bagalkot districts, Karnataka (India) using serial dilution pour plate method. These isolates were ascribed to two species namely Trichoderma harzianum (Th) and Trichoderma viride (Tv) based on cultural and morphological characterisation. The isolates were evaluated against major soil borne pathogens causing rhizome rot in turmeric and ginger viz., Pythium, Fusarium, Rhizoctonia and Sclerotium sp., by dual culture method. Isolate Tv-23 was recorded highest inhibition of Pythium (83.19 %). Isolate Tv-17 had shown maximum per cent inhibition of mycelia growth of Fusarium (90.92 %) and Rhizoctonia (89.56 %). Isolate Th-25 was most aggressive and able to inhibit 79.04 per cent of Sclerotium growth. Based on the antagonistic activity of all Trichoderma isolates tested against soil borne pathogens, eight isolates viz., Tv-1, Tv-2, Tv-8, Tv-14, Tv-17, Tv-23Th-18 and Th-25 were found to show highest per cent inhibition.